Potential groundwater exploration in use of 2-D Electrical Resistivity Tomography (ERT) techniques at the Department of Agriculture Kelantan Research and Developmental platform Padang Raja Kelantan - Fazlil Ilahi, Wan Fazilah; Abu Hassan, Nur Hidayu; Ismail, Mohd Razi; Che'ya, Nik Norasma; Berahim, Zulkarami; Omar, Mohamad Husni; Zakaria, Nurul Idayu; Mohamed Zawawi, Mohamed Azwan (Universiti Putra Malaysia Press, 2021)
2-D electrical resistivity has been a proper investigation survey for determination of subsurface geophysical in describing the complex features geology profile. In this study, an electrical resistivity survey was conducted at paddy cultivation area located in Melor, Kelantan, Malaysia. Since the end plot of paddy field experiences water scarcity especially during dry season, there is a need to find other alternative water source. The study was conducted on 1st and 2nd February 2020 to identify zone area of groundwater for Melor, Kelantan. Four resistivity lines using Induced Polarization (IP) and 2-D Electrical Resistivity Imaging Technique were conducted using a set of ABEM Terrameter SAS4000. Short resistivity survey was applied to gained detail of subsurface formation near the ground, while the longer resistivity survey was applied to obtain deeper subsurface delineation. Measured data obtained was analyzed using RES2DINV software and result of contrast resistivity values was used to determine the geological structures, while the chargeability values were analyzed accordingly to determine area of expected potential groundwater zone. Results from the resistivity profiles show a range values of 0 Ωm to 50,000 Ωm with total maximum acquired depth of 65.6 m below ground surface. The chargeability profiles show a range values of 0 msec to 500 msec, that shows potential of groundwater zone area lies at 0 to 4 msec. It was found that at a depth of 60 to 75 m, 30 m from center of Profile B was suitable for a production well which was expected to be a potential area for groundwater zone.